STRATEGIC MANAGEMENT DRIVERS AND PERFORMANCE OF THE KENYA OWNED TOURISM STATE CORPORATIONS THE MEDIATING ROLE OF STRATEGY IMPLEMENTATION - Muthoka, Miriam; Oloko, Dr.Margaret; Obonyo, Dr.Levi (European Journal of Business and Strategic Management, 2017)
Purpose: This study sought to provide an opportunity to test the strategic management drivers of performance and the mediating role of strategy implementation by looking at information technology driver, strategic planning driver, change management driver, organizational leadership driver and the mediating role of strategy implementation. Methodology:The study employed descriptive and cross-sectional research designs. The target population comprised all the Tourism state owned corporations in Kenya with the management of these firms being the respondents. A census study was carried out due to small nature of the target population. Data collection involved the use of questionnaires which attracted both quantitative and qualitative responses. The respondents were all the Chairmen, CEO, managers and assistant managers of all Tourism state corporations in Kenya. These data was analyzed using content analysis for qualitative data. The quantitative data was analyzed using regression analysis. ANOVA test was carried out to test the significance of the model. Results:The findings of the study indicated that information technology drivers, strategic planning drivers, change management drivers and Organizational leadership drivers have a positive effect on performance in the Tourism state corporations in Kenya. Policy recommendation:. The study also recommended that Tourism state corporations in Kenya should develop smart goals and objectives, have and enact sustainable action plans and formulate clear initiatives and consensus building because of their positive effect on performance. Further studies can be done to ascertain the effect of strategic management drivers and the mediating role of strategy implementation in other state corporations in Kenya other than the tourism sector.